The Effect of Sharia Financing Availability on Economic Growth of MSMEs in Sukabumi - Moh Gifari Sono; Eko Sudarmanto; Dyah Palupiningtyas; Efendi Sugianto (Westscience Press, 2023)
This research investigates the effect of the availability of Islamic financing on the economic growth of Micro, Small, and Medium Enterprises (MSMEs) in Sukabumi. A sample of 197 MSMEs participated in the study, providing data on Islamic financing utilization, financial performance indicators, and other relevant variables. The analysis employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the relationships between these variables. The results reveal a significant and positive relationship between the availability of Islamic financing and the economic growth of MSMEs. Additionally, the study uncovers the mediating role of financial performance indicators, indicating that improved financial performance acts as a mechanism through which Islamic financing positively influences economic growth. Furthermore, the moderation analysis highlights the varying impact across different enterprise sizes, with medium-sized enterprises experiencing a more pronounced positive effect. The practical implications of these findings are discussed in the context of policy, financial institutions, and MSME owners. Policymakers can use the results to design targeted policies, financial institutions can refine their strategies, and MSME owners gain insights into the benefits of utilizing Islamic financing.